2006
DOI: 10.1039/b612660j
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic frameworks exhibiting strong anion–π interactions

Abstract: Coordination polymers offer a significant potential for applications in adsorption, guest and anion recognition and sensing. Their structure commonly provides binding sites for such specific interactions as pi-pi stacking and XH...pi hydrogen bonding. The latter reflects the ability of the pi-cloud to interact with positively polarized atoms. An electrostatic interaction between anionic species and electron deficient heterocycles, which parallels the above binding scheme, is also possible and very recently the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…11.5) based on 1,4,5,8,9, 12-hexaazatriphenylene (HAT) substituted with cyano groups that is able to interact with three anions by one side of the polycyclic ring and with one anion by the opposite site [93]. Moreover, it is easily available by a one-pot syn thesis involving inverse electron demanding Diels-Alder cycloaddition [95]. It was concluded that the formation of typical anion-π non-covalent complexes, charge transfer complexes, or electron transfer adducts strongly depends on the type of anion.…”
Section: Physical Naturementioning
confidence: 99%
See 2 more Smart Citations
“…11.5) based on 1,4,5,8,9, 12-hexaazatriphenylene (HAT) substituted with cyano groups that is able to interact with three anions by one side of the polycyclic ring and with one anion by the opposite site [93]. Moreover, it is easily available by a one-pot syn thesis involving inverse electron demanding Diels-Alder cycloaddition [95]. It was concluded that the formation of typical anion-π non-covalent complexes, charge transfer complexes, or electron transfer adducts strongly depends on the type of anion.…”
Section: Physical Naturementioning
confidence: 99%
“…The pyridazino [4,5-d]pyridazine ligand (L pp ) has been utilized by Gural'skiy et al [95] to investigate the ability of this ring to establish anion-π interactions providing an attractive structural synthon and an unique π-bifunctional building block for novel polymeric and molecular anion receptors. Two examples are represented in Figure 11.7.…”
Section: Physical Naturementioning
confidence: 99%
See 1 more Smart Citation
“…Although Ag(I) ion is a particularly good candidate for the flexible coordinative tendencies of sulfonate anion, there is limited structures about arenedisulfonate complexes involving the Ag(I) ion and such complexes modified by N-donor ligands [16,17]. On the other hand, 2-aminopyrimidine-type ligands possessing potential hydrogen bond and p-electron donors usually form diverse nonvalent interactions such as hydrogen-bonding, pÁ Á Áp stacking, C-HÁ Á Áp and anionÁ Á Áp interactions [18][19][20][21], and are widely used in designing coordination polymers (CPs) by us [22][23][24][25][26][27][28][29] and others [30,31]. As extended work, we introduced 1,5-naphthalenedisulfonic acid (H2nds) as an auxiliary ligand into our previous systems and successfully obtained two new 2D CPs, namely [Ag(apym)(nds) 0.5 ] n (1) and [Ag(dmapym)(nds) 0.5 ] n (2) (apym = 2-aminopyrimidine, dmapym = 2-amino-4,6-dimethylpyrimidine, H2nds = 1,5-naphthalenedisulfonic acid).…”
Section: Introductionmentioning
confidence: 99%
“…Since coordination of the heterocycle to the metal ions enhances the ability for the anion···π interactions [4], this phenomenon is relevant for the solid-state coordination chemistry as an important factor governing disposition of counter anions, their recognition and selective binding [5]. It was considered as a design tool for the generation of supramolecular structures involving different types of π···anion···π and anion···π···anion sandwiches [6,7], double interactions with polycyclic receptors [8], anion···π and hydrogen bonding [7] and combined anion···π, lone pair···π and π/π interactions [9]. The cooperative effect of these forces is particularly prevalent for the anions located in the predefined cages with π-acidic surface [10] and therefore such systems themselves provide a useful probe for studying the weaker anion···π and lone pair···π bonding.…”
mentioning
confidence: 99%